NILAI-NILAI EKONOMI HUBUNGAN MANUSIA DENGAN TUHAN DALAM PELAKSANAAN TRIHITAKARANA DI DESA PAKRAMAN KABUPATEN GIANYAR - Sukarsa, I Made (PIRAMIDA; Vol. 2, No. 1 Juli 2006, 2012)
In an effort to achieve life objective, human beings need social interaction with their environment. Life objective of Balinese community (Hindu) as stated in Bhagawad Gita is ?Moksrtham Jagathita ya Caiti Dharma?, that is achieving moksa trough truth way of moksa abstractly, which means unite with Ida Sang Hyang Widhi Wasa. In reality, moksa mean ?sukha tan pawali duka?. For achieving this, human being try to keep harmonic relationship among three elements i.e. relationship among human being, relationship with their environment, and relationship with god. The implementation of the relationship of the three elements is trough yadnya expenditure, known as panca yadnya. For instance, dewa yadnya expenditure is for keeping relationship between human being and god, butha yadnya is for keeping relationship between human being and his environment, and manusa yadnya is for keeping relationship among human beings. Aims of this study including four matters : 1) identification of kind of ceremony (dewa yadnya) for six month, 2) kind and quantity of material used, 3) time spent and number of labor used, 4) value of money (Rupiah) spend for the ceremonies. This study done in Gianyar regency with sample of 52 Hindu households in five pekraman villages and 30 banjar adat. Household sample and village sample are choosen by using stratified random sampling. The findings shows that 1) the number of household offering in Gianyar Regency in every rerahinan day is 42,46 units; 2) material of dewa yadnya consist of at least 21 kinds or equal to 13,535.98 ton per year. Among other, 2999.78 ton of flower; 5521.26 ton of coconut leafe and , 1824.58 ton of coconut; 3) time spent for running cremation ceremony from preparation until the ?D? day is 5531 effective hours, consist of 3,032 man hour and 2,499 woman hour, or 699 mandays wich is consist of 386,44 mandays (man) and 312,38 mandays (woman; 4) Total expenditure (Gianyar regency) for yadnya is Rp. 651.877.818.490. On average, for every household this amount of money is used for keeping good relationship among them (manusa yadnya) about Rp. 4,791,693.47, for butha yadnya is about Rp. 164,615.38, and for dewa yadnya is about Rp. 3,618,328.08.,-
Keywords: ritual, spiritual economics